Challenges of Human Rights Abuses in Nigerian Democratic Governance – Which Way Forward ? - Adenrele, Adetoro Rasheed; Olugbenga, Omiyefa Muraina (Journal of Social Economics Research, 2014)
The Universal Declaration of Human Rights (UDHR) was unanimously adopted and proclaimed by the United Nations through the General Assembly Resolution 217A(111) on the 10th of December, 1948. Since its declaration, it has become fashionable for most countries of the world (Nigeria inclusive) to entrench the catalogue of rights in their national constitutions. Regrettably, in Nigeria and indeed in Africa, people are usually subjected to physical and mental torture. The case of accidental discharges, domestic violence, detention without trial, kidnappings, and police brutality are common occurrences. In short, the Nigerian experience has shown the level at which peoples’ integrity and dignity are not respected and protected in the society. It is against this backdrop that this paper examines the challenges of human rights abuses in Nigeria. It also explores some conceptual clarifications and further examines various threats to human rights in Nigerian society. The paper concludes by recommending among others, the strengthening of independence of the judiciary, press freedom, democratic rules/principles, human rights education and public vigilance to curtail human rights abuses and promote good governance in Nigeria.